Preventive Treatments for Psychosis: Umbrella Review (Just the Evidence) - Fusar-Poli, Paolo; Davies, Cathy; Solmi, Marco; Brondino, Natascia; De Micheli, Andrea; Kotlicka-Antczak, Magdalena; Shin, Jae Il; Radua, Joaquim (Frontiers in Psychiatry, 2019)
Background Indicated primary prevention in young people at Clinical High Risk for Psychosis (CHR-P) is a promising avenue for improving outcomes of the most severe mental disorders; their effectiveness has recently been questioned. Methods Umbrella review. A multi-step independent literature search of Web of Science until January 11th, 2019 identified interventional meta-analyses in CHR-P individuals. The individual RCTs that were analysed by the meta-analyses were extracted. A review of ongoing trials and a simulation of living meta-analysis complemented the analysis. Results Seven meta-analyses investigating preventive treatments in CHR-P individuals were included. None of them produced pooled effect sizes across psychological, pharmacological or other types of interventions. The outcomes analysed encompassed: risk of psychosis onset, the acceptability of treatments, the severity of attenuated positive/negative psychotic symptoms, depression, symptom-related distress, social functioning, general functioning, and quality of life. These meta-analyses were based on 20 RCTs: the vast majority defined the prevention of psychosis onset as their primary outcome of interest and only powered to large effect sizes. There was no evidence to favour any preventive intervention over any other (or control condition) for improving any of these clinical outcomes. Caution is required when making clinical recommendations for the prevention of psychosis in CHR-P individuals. Discussion Prevention of psychosis from a CHR-P state has been and should remain, the primary outcome of interventional research, refined and complemented by other clinically meaningful outcomes (severity of symptoms, functional status, recovery, quality of life). Stagnation of knowledge should promote innovative and collaborative research efforts, in line with the progressive and incremental nature of medical knowledge. Advancements will most likely be associated with the development of new experimental therapeutics that are ongoing, along with the ability to deconstruct the high CHR-P heterogeneity. This would require the estimation of treatment-specific effect sizes through living individual participant data meta-analyses, controlling risk enrichment during recruitment, statistical power and embedding precision medicine within youth mental health services that can accommodate sequential prognosis and advanced trial designs. Conclusions The evidence-based challenges and proposed solutions addressed by this umbrella review can inform the next generation of research into preventive treatments for psychosis.